Showing Identity and Proudness as Black Women in Three Poems I am a Black Woman (1970) by Mari Evans, A Woman Speaks (1997) by Audre Lorde, I am More Than That (2018) by Lindiwe Princess Maseko. - Fadilah Husna; Leni Marlina (Universitas Negeri Padang, 2020)
This analysis of the three poems I am a Black Woman (1970) by Mari Evans, A Woman Speaks (1997) by Audre Lorde, I am More Than That (2018) by Lindiwe Princess Maseko are expose the issues about showing identity and proudness as Black women. It is also expose the contribution of poetic elements (speaker, repetition, and tone) in revealing the issues about showing identity and proudness of Black women. This analysis is done by through text-based and context-based interpretation that is related to the concept of power and knowledge by Michel Foucault. The result of this analysis is exposing about the pronouncement of Black women about their identity and their proudness. Showing identity as Black women is live with culture of Black. Showing proudness of being Black women is respecting their original identity as Black.